Services trade and credit frictions: Evidence with matched bank–firm data. (14th February 2020) - Bripi, Francesco; Loschiavo, David; Revelli, Davide
Abstract: The effects of credit supply shocks on the exports of services are not clear a priori. On the one hand, services need lower initial investment in physical capital than manufacturing. On the other hand, competitiveness for exporting services requires investments in intangible capital and in product customisation that may be subject to credit frictions. Using Italian matched bank–firm data and focusing on the sovereign debt crisis, we find an elasticity of services exports to credit supply, between 0.3 and 0.4. The effects of credit shocks are especially relevant for firms exporting complex services to countries with weaker institutions and for services that are not the main product of the firms. Overall, our results suggest that credit supply plays a relevant role for exporting services during crises.